2023
DOI: 10.3389/fncel.2022.1067570
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the progress and impact of ferroptosis in hemorrhagic stroke

Abstract: Hemorrhagic stroke is a devastating cerebrovascular disease with high morbidity and mortality, for which effective therapies are currently unavailable. Based on different bleeding sites, hemorrhagic stroke can be generally divided into intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH), whose pathogenesis share some similarity. Ferroptosis is a recently defined programmed cell deaths (PCDs), which is a critical supplement to the hypothesis on the mechanism of nervous system injury after hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…Of note, ferroptosis is a ROS-dependent form of cell death characterized by iron accumulation and lipid peroxidation [ 5 , 22 ] The lipid peroxidation is a free radical-driven reaction that primarily affects polyunsaturated fatty acids in cell membranes, the product of which gradually increases during ferroptosis, from the initial lipid hydroperoxides (LOOHs) to the later production of malondialdehyde (MDA) and 4-hydroxynenoals (4-HNE) [ 5 , 6 ]. Disruption of the antioxidant systems is contributed to overproduction and accumulation of lipid peroxidation products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, ferroptosis is a ROS-dependent form of cell death characterized by iron accumulation and lipid peroxidation [ 5 , 22 ] The lipid peroxidation is a free radical-driven reaction that primarily affects polyunsaturated fatty acids in cell membranes, the product of which gradually increases during ferroptosis, from the initial lipid hydroperoxides (LOOHs) to the later production of malondialdehyde (MDA) and 4-hydroxynenoals (4-HNE) [ 5 , 6 ]. Disruption of the antioxidant systems is contributed to overproduction and accumulation of lipid peroxidation products.…”
Section: Discussionmentioning
confidence: 99%
“…Another efficient endogenous antioxidant system is the ferroptosis suppressor protein 1 (FSP1)/coenzyme Q10 (CoQ10) pathway [ 12 ]. FSP1 uses the reducing equivalents of NADP [NAD(P)H] to reduce CoQ10 to ubiquinol, which acts as a lipophilic radical-trapping antioxidant to remove lipid peroxides from phospholipid bilayers [ 12 , 22 ]. In our study, we demonstrated that GSH deletion and MDA accumulation in SAH was improved by Fer-1treatment, the mechanism under which may be associated with both GSH/GPX4 and FSP1/CoQ10 antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, ferroptosis is characterized by mitochondrial contraction and increased mitochondrial membrane density. 56,57 Unlike other cell death types, there is no cell swelling or membrane rupture, and no changes in the nucleus or chromatin contraction are observed. Biochemically, ferroptosis involves the aggregation of reactive oxygen species and iron ions, activation of the mitogen-activated protein kinase (MAPK) system, reduced cystine uptake, depletion of glutathione, and inhibition of system Xc − , among others.…”
Section: Ferroptosis and Its Process Overview Of Ferroptosismentioning
confidence: 99%
“…Biochemical and transcriptomic analyses of mediators of iron metabolism, antioxidant defenses, oxidative stress, and lipid peroxidation in experimental disease models, autopsy material, and induced pluripotent stem cell (iPSCs) derived from patients indicate that ferroptosis is a major mechanism of cell death in a wide range of neurologic disorders. These include Alzheimer disease (AD), 64,72,76-82 Parkinson disease (PD), 55,83-87 amyotrophic lateral sclerosis (ALS), 88-92 Huntington disease, 93-95 Friedreich ataxia, 96-98 multiple sclerosis, 99-101 ischemic stroke, 47,102-105 intracerebral hemorrhage, 106,107 traumatic brain injury, 108 spinal cord injury, 109,110 epilepsy, 111-113 and glioma, 114 among others. This topic has been extensively reviewed, 16-21,115,116 and only few concepts will be emphasized in this study.…”
Section: Role Of Ferroptosis In Neurologic Diseasementioning
confidence: 99%